Phylogenetic distribution and expression pattern analyses identified a divergent basal body assembly protein involved in land plant spermatogenesis. Issue 3 (3rd August 2022) - Koshimizu, Shizuka; Minamino, Naoki; Nishiyama, Tomoaki; Yoro, Emiko; Sato, Mayuko; Wakazaki, Mayumi; Toyooka, Kiminori; Ebine, Kazuo; Sakakibara, Keiko; Ueda, Takashi; Yano, Kentaro
Summary: Land plant spermatozoids commonly possess characteristic structures such as the spline, which consists of a microtubule array, the multilayered structure (MLS) in which the uppermost layer is a continuum of the spline, and multiple flagella. However, the molecular mechanisms underpinning spermatogenesis remain to be elucidated. We successfully identified candidate genes involved in spermatogenesis, deeply divergent BLD10 s, by computational analyses combining multiple methods and omics data. We then examined the functions of BLD10 s in the liverwort Marchantia polymorpha and the moss Physcomitrium patens . Mp BLD10 and Pp BLD10 are required for normal basal body (BB) and flagella formation. Mp bld10 mutants exhibited defects in remodeling of the cytoplasm and nucleus during spermatozoid formation, and thus Mp BLD10 should be involved in chromatin reorganization and elimination of the cytoplasm during spermiogenesis. We identified orthologs of MpBLD10 and PpBLD10 in diverse Streptophyta and found that MpBLD10 and PpBLD10 are orthologous to BLD10/CEP135 family proteins, which function in BB assembly. However, BLD10s evolved especially quickly in land plants and MpBLD10 might have acquired additional functions in spermatozoid formation through rapid molecular evolution.